2021
DOI: 10.46490/bf558
|View full text |Cite
|
Sign up to set email alerts
|

The impact of ash dieback on veteran trees in southwestern Sweden

Abstract: Ash dieback (Hymenoscyphus fraxineus) is a fungal disease which affects ash throughout Sweden.  Monitoring to study of the impact of ash dieback on veteran trees was undertaken in southwest Sweden in 2009, 2011, 2013, 2015, and 2020. The study found that 94.5% of the ash trees observed were affected by ash dieback disease in 2020 compared with 62% in 2009.  70 of the studied ash trees have died (21%) since the monitoring began. In 2009 there was no relationship between girth and ash dieback, but in 2020 the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
1
0
0
Order By: Relevance
“…This provides robust evidence to answer yes to the second question: trees in a more vigorous condition had greater resistance to the disease. This result is compatible with earlier studies based on less precise evidence that showed a negative relationship between the severity of ADB and tree 'vitality' in Scandinavia (Bengtsson et al, 2021;Timmermann et al, 2017), and the conclusion of Skovsgaard et al (2017) that vigorous trees can better compensate for the effects of H. fraxineus. Previous studies have also shown that tree height can be a significantly strong predictor of lower rates of ADB defoliation (Erfmeier et al, 2019), as well as individual tree vigour (Dobbertin, 2005), and our result that lower ADB severity is significantly associated with a larger diameter at breast height matches the findings of previous studies (e.g.…”
Section: Ta B L Esupporting
confidence: 92%
“…This provides robust evidence to answer yes to the second question: trees in a more vigorous condition had greater resistance to the disease. This result is compatible with earlier studies based on less precise evidence that showed a negative relationship between the severity of ADB and tree 'vitality' in Scandinavia (Bengtsson et al, 2021;Timmermann et al, 2017), and the conclusion of Skovsgaard et al (2017) that vigorous trees can better compensate for the effects of H. fraxineus. Previous studies have also shown that tree height can be a significantly strong predictor of lower rates of ADB defoliation (Erfmeier et al, 2019), as well as individual tree vigour (Dobbertin, 2005), and our result that lower ADB severity is significantly associated with a larger diameter at breast height matches the findings of previous studies (e.g.…”
Section: Ta B L Esupporting
confidence: 92%